Learning as an educational priority? - Kaminska Malgozhata (Borys Grinchenko Kyiv Metropolitan University, 2017)
A man should learn at school how to learn, how to search for information, how to build knowledge and how to use it. Researchers and strategists who are responsible for the shape of a modern and efficient European education are convinced of this. Does education in Polish schools create favorable conditions for such learning What should be changed to become involved in the process of adapting to the real needs, signaled in the social and economic area as soon as possible? What can be classified as the positive symptoms of reaction to changes in work and education of people in Poland, Europe and around the world? The author of the text attempts to formulate subjective answers to these questions not only by basing on her own reflections and resulting from observations of the surrounding reality, but also using the results of educational research and interviews with analysts and pedagogy researchers.